Optical Waveguides and Terahertz Signal by Finite Element Method: A Survey - Smitha, T. V.; S, Madhura; N, Shreya; Udupa, Sahana (IRO Journal on Sustainable Wireless Systems, 2021)
This paper examines the use of the Finite Element Method (FEM) in the field of optical waveguides and terahertz signals, with the main goal of explaining how this method aids in recent advances in this field. The basics of FEM are briefly reviewed, and the technique's application to waveguide discontinuity analysis is observed. Second-order and higher-order derivatives result from optical waveguide modeling, which is significant for information exchange and many other nonlinear phenomena. The use of FEM in the improvised design of hexagonal sort air hole porous core microstructure fibers, which produces hexagonal structure cladding and rectangular-shaped air holes in the fiber core for excellent terahertz signal transmission, was also observed. These modifications were intended to improve the fiber's properties in comparison to other structures. This approach verifies that the fiber has high birefringence, low material loss, a high-power fraction, and minimal dispersion varia-tion. The features of square-type microstructure fiber are investigated. A folded-shaped po-rous cladding design is recognized for sensing applications. This type of photonic crystal fiber is also known as FP-PCF since it features circular air holes. The most approximate findings of this application are obtained using FEM. In comparison to many other approach-es for various applications, it is evident that FEM is a powerful and numerically efficient tool. This work does a survey of optical waveguides and terahertz signals using the Finite Element Method. Terahertz signals can be used in conjunction with electromagnetic waves to identify viruses. Thus, Terahertz signals are employed in real-world applications such as fuel adulteration, liquid metal synthesis, and virus detection.